PENDIDIKAN KARAKTER SISWA KELAS VII MELALUI PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM DI MTS NURUL MUSTHAFA KOTABARU - Mahfuz, Ahmad; Fitrianoor, Wahyu; Fadillah, Nor; Juhsairiyah, Juhsairiyah (ADDABANA: Jurnal Pendidikan Agama Islam, 2020)
Abstract: This research discusses "Character Education of Students VII Through Learning Islamic Cultural History". The formulation of the problem in this study is How is the process of implementing learning carried out by Islamic cultural history teachers in shaping student character through learning Islamic cultural history at MTs. Nurul Musthafa Kotabaru. What are the supporting and inhibiting factors in the character building of seventh grade students through the learning process of Islamic cultural history at MTs. Nurul Musthafa Kotabaru.The subjects of this research are Islamic cultural history subject teachers, Head of Madrasah, and seventh grade students at MTs Nurul Musthafa, the object of this research is Character Education of seventh grade students through Islamic cultural history learning at MTs Nurul Musthafa Kotabaru. as well as supporting and inhibiting factors in Character Education of seventh grade students through Islamic Cultural History Learning at MTs Nurul Musthafa Kotabaru. In extracting data, researchers use qualitative descriptive types and approaches, interview techniques, observation and documentation. Data processing techniques are carried out by collecting data, classifying data, editing and interpreting data, then analyzing with qualitative descriptive analysis and drawing conclusions inductively.The results of the research The process of implementing Islamic cultural history learning includes learning planning, learning implementation and learning evaluation, learning Islamic cultural history for student character building has gone well and as expected. This is evidenced by the increase in student character in Islamic cultural history lessons by making the Prophet Muhammad SAW a good role model including compassion for others, religion, honesty, diligence, responsibility, tolerance, and discipline. Supporting and inhibiting factors in the process of implementing character education in the learning process of Islamic cultural history are: teacher, family, environment and student factors. Keywords: Character Education, Students, Islamic Cultural History. Abstrak: Penelitian ini membahas tentang “Pendidikan Karakter Siswa VII Melalui Pembelajaran Sejarah Kebudayaan Islam”. Rumusan masalah dalam penelitian ini adalah Bagaimana proses pelaksanaan pembelajaran yang dilakukan guru sejarah kebudayaan Islam dalam pembentukan karakter siswa melalui pembelajaran sejarah kebudayaan Islam di MTs. Nurul Musthafa Kotabaru. Apa saja faktor pendukung dan penghambat dalam pembentukan karakter siswa kelas VII melalui proses pembelajaran sejarah kebudayaan Islam di MTs. Nurul Musthafa Kotabaru.Subjek penelitian ini adalah guru mata pelajaran sejarah kebudayaan Islam, Kepala Madrasah, dan siswa kelas VII di MTs Nurul Musthafa, Objek pada penelitian ini yaitu Pendidikan Karakter Siswa Kelas VII Melalui Pembelajar sejarah kebudayaan Islam di MTs Nurul Musthafa Kotabaru. serta faktor pendukung dan penghambat dalam Pendidikan Karakter Siswa Kelas VII Melalui Pembelajaran Sejarah Kebudayaan Islam di MTs Nurul Musthafa Kotabaru. Dalam penggalian data, peneliti menggunakan jenis dan pendekatan deskriftif kualitatif, teknik wawancara, observasi dan dokumentasi. Teknik pengolahan data dilakukan dengan pengumpulan data, klasifikasi data, editing dan interpretasi data, selanjutnya dianalisis dengan analisis deskriptif kualitatif dan ditarik simpulan dengan induktif.Hasil penelitian Proses pelaksanaan pembelajaran sejarah kebudayaan Islam meliputi perencanaan pembelajaran, pelaksanaan pembelajaran dan evaluasi pembelajaran, pembelajaran sejarah kebudayaan Islam untuk pembentukan karakter siswa sudah berjalan dengan baik dan sesuai yang diharapkan. Hal ini terbukti dengan adanya peningkatan karakter siswa pada pelajaran sejarah kebudayaan Islam dengan menjadikan Nabi Muhammad SAW sebagai suritauladan yang baik diantaranya yaitu kasih sayang terhadap sesama, religius, jujur, rajin, tanggung jawab, toleransi, dan disiplin. Faktor pendukung dan penghambat dalam proses pelaksanaan pendidikan karakter dalam proses pembelajaran sejarah kebudayaan Islam yaitu: faktor guru, keluarga, lingkungan dan siswa. Kata Kunci: Pendidikan Karakter, Siswa, Sejarah Kebudayaan Islam.